Reforma systemu zabezpieczeń i weryfikacji materiałów jądrowych jako warunek bezpieczeństwa nuklearnego w XXI w. (Politeja, 2016)
The reform of the nuclear safeguards and verification of nuclear materials as a condition of nuclear safety in the 21 CenturyThe condition of maintaining nuclear safety in the twentieth century is to ensure a global system of nuclear materials safeguards. In practice, this means the need for a global system of verification of compliance with non‑proliferation requirements equipped with mechanisms of international control, accounting and physical protection of nuclear materials and facilities, as means of preventing the usage of nuclear dual‑use technology for non‑peaceful purposes (construction of nuclear weapons or other nuclear explosive devices). The track record of non‑proliferation regime discovered the weakness of the nuclear safeguards and verification system, in particular, limits of the IAEA control functions. Maintaining the “Nuclear Peace” can be assured only by a global system of physical protection, accounting, and security of nuclear materials, which means the need to improve the internationally comprehensive system of verification of compliance with non‑proliferation. The aim of the article is to present the principles of the international system of nuclear safeguards and the role of the International Atomic Energy Agency in maintaining nuclear peace and nuclear challenges of non‑proliferation regime reform. The analysis leads, among others, to the conclusion that the Agency should develop a procedure to standardize the rules, structure, and terminology of reporting non‑compliance, promote the internationalization of the fuel cycle while the UN Security Council should react faster in the case of non‑compliance detection.